Chronic stress drives ovarian cancer progression via myeloid-derived suppressor cells infiltration and Notch signaling pathway activation - Rivera-López, Yadiel A.; Torres-Rosado, Alanis P.; Casiano-Martínez, Jaydiel A.; Meléndez-Rodríguez, Luinet L.; Imad-Hamad, Raian; Hernández-Carrasquillo, Sofía M.; Rivera-Pérez, Luis M.; Ortiz-León, Melanie; Torres-Rodríguez, Orlando I.; Aquino-Acevedo, Alexandra N.; Castillo-Ocampo, Yesenia; Duffey, Grace; et al. (Frontiers in Immunology, 2025)
BackgroundOvarian cancer (OC) is a leading cause of cancer-related death among women, with elevated levels of stress hormones linked to OC progression and immune evasion in the tumor microenvironment (TME). Chronic psychosocial stress has been associated with the expansion of immunosuppressive myeloid-derived suppressor cells (MDSCs), which promote tumor growth and negatively impact patient outcomes. This study tested how chronic daily restraint stress affected ovarian cancer progression, Notch signaling, and MDSCs in the OC TME. We hypothesized that chronic stress increases MDSCs infiltration in the TME, enhances Notch signaling in OC cells, and promotes cancer progression. MethodsFemale C57BL/6 mice were injected with ID8Luc or IG10Luc OC cells and subjected to daily restraint stress. We also isolated bone marrow from naïve C57BL/6 mice to differentiate myeloid cell precursors into MDSCs. These cells were then exposed to norepinephrine (NE), epinephrine (EPI), or corticosterone (CC). To further evaluate the effects of stress hormones on the dysregulation of the Notch signaling pathway, we treated OC cells with NE, EPI, or CC.ResultsChronic daily restraint stress increased MDSCs infiltration and enriched polymorphonuclear (PMN)-MDSCs in the TME and bone marrow in both models. Ex vivo studies demonstrated an increased enrichment of PMN-MDSCs along with a reduction of mononuclear (M)-MDSCs in the groups treated with stress hormones, particularly CC. Our results showed that stress hormones significantly increased the expression of notch intracellular domain (NICD) in OC cells. Additionally, we observed increased mRNA levels of Notch1, Jagged2, and Hes1, along with elevated NICD and HES1 protein levels, mediated by CC-induced GSK3β phosphorylation. Pharmacological inhibition of NICD and gLucocorticoid receptors blocked the CC-induced Notch pathway activation via GSK3β phosphorylation. Moreover, tumors from mice subjected to restraint stress had elevated expression of Notch1, Jagged 2, NICD, HES1, GR, ADRB2, and pS9-GSK3β. ConclusionThese data indicate that chronic stress leads to MDSCs infiltration and suppressive activity, which contributes to an immunosuppressive TME and OC progression.